A retrospective review of all children admitted with acute severe asthma to the paediatric intensive care unit, Red Cross War Memorial Children's Hospital between 2009-2019. - Salie, Moegamad (Department of Paediatrics and Child Health, 2024)
Background and Aim Asthma is one of the commonest chronic conditions of childhood and affects children worldwide. The majority of children who experience an acute exacerbation of asthma do not require admission to a paediatric intensive care unit (PICU). There is limited data on the admission rates, treatment modalities and length of PICU stay, for children who have acute severe asthma (ASA) in a South African context. In this study, we aim to describe the patient profiles and treatment of all children admitted to the PICU with ASA. Method We conducted a retrospective audit of all children admitted with ASA to the paediatric intensive care unit at Red Cross War Memorial Children's Hospital in Cape Town, South Africa between 01 January 2009 - 31 December 2019. Results There were 14592 PICU admissions over the 11-year period, of which 180 admissions (1,2%) were for acute severe asthma. There were 96 male (53,3%) admissions and the median, interquartile range (IQR) age on admission was 67 (37 – 93) months. Nearly all the patients received nebulisations, steroids, and magnesium sulphate before PICU admission. Half of the patients were loaded with IV salbutamol (n=96; 53,3%) and about a third (n=61; 34%) received a salbutamol infusion before admission to PICU. Similar proportions received nebulisations and steroids in PICU, 34 patients (19%) received magnesium sulphate again in PICU and a total of 130 patients (72,2%) received a salbutamol infusion. Most children received non-invasive respiratory support (n=167; 90,3%), and 18 children (9,7%) required mechanical ventilation for a median (IQR) of 3 (2 – 4) days. The median PICU stay was 1 (IQR 1 – 2) days and median hospital stay was 4 (IQR 3 – 6) days. No children died. Conclusion There has been an increasing number of children admitted to PICU with ASA over the 11- year period. There has been increased utilization of non-invasive ventilation (NIV) strategies, mainly HFNC and the duration of PICU support is short.